2021
DOI: 10.1136/gutjnl-2021-325036
|View full text |Cite
|
Sign up to set email alerts
|

Unannotated small RNA clusters associated with circulating extracellular vesicles detect early stage liver cancer

Abstract: ObjectiveSurveillance tools for early cancer detection are suboptimal, including hepatocellular carcinoma (HCC), and biomarkers are urgently needed. Extracellular vesicles (EVs) have gained increasing scientific interest due to their involvement in tumour initiation and metastasis; however, most extracellular RNA (exRNA) blood-based biomarker studies are limited to annotated genomic regions.DesignEVs were isolated with differential ultracentrifugation and integrated nanoscale deterministic lateral displacement… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 40 publications
1
28
0
Order By: Relevance
“…Similar to ctDNA, EV and its cargoes are regarded as promising biomarkers to augment current HCC surveillance methods due to their early presence in circulation [81] . Our recent phase 2 biomarker study applied an HCC EV Digital Scoring Assay to quantify the identified 10 HCC-specific mRNA markers [74] from purified HCC EVs and showed the resultant digital scores could noninvasively detect BCLC stage 0-A HCC from cirrhosis with an AUROC of 0.93 (sensitivity = 94%, specificity = 89%) [82] . Currently, almost all of the existing EV-based biomarker studies are still at phase II (case-control) [81,83] , further phase III (prospective specimen collection, retrospective blinded evaluation), and phase IV studies (prospective cohort) are required to validate their performance for detecting early-stage HCC [80] .…”
Section: Liquid Biopsymentioning
confidence: 99%
“…Similar to ctDNA, EV and its cargoes are regarded as promising biomarkers to augment current HCC surveillance methods due to their early presence in circulation [81] . Our recent phase 2 biomarker study applied an HCC EV Digital Scoring Assay to quantify the identified 10 HCC-specific mRNA markers [74] from purified HCC EVs and showed the resultant digital scores could noninvasively detect BCLC stage 0-A HCC from cirrhosis with an AUROC of 0.93 (sensitivity = 94%, specificity = 89%) [82] . Currently, almost all of the existing EV-based biomarker studies are still at phase II (case-control) [81,83] , further phase III (prospective specimen collection, retrospective blinded evaluation), and phase IV studies (prospective cohort) are required to validate their performance for detecting early-stage HCC [80] .…”
Section: Liquid Biopsymentioning
confidence: 99%
“…60 EVs are promising biomarkers for early HCC detection evidenced by the increasing number of studies published. [61][62][63][64][65] As key mediators of intercellular communication EVs are present in the circulation at early stages of disease. 66,67 One study in 158 patients with HCC that a 10-gene molecular signature had 94% sensitivity and 89% specificity in detecting early HCC.…”
Section: Data On Clinical Applications Of Liquid Biopsy For Hcc Early...mentioning
confidence: 99%
“…62 von Felden et al identified a 3-small RNA clusters signature overexpressed in plasma exosomal RNA of 157 patients with HCC (p < 0.01). 63 This biomarker was then independently validated in phase 2 case-control studies in 209 patients (including 105 with early stage HCC) and demonstrated 86% sensitivity and 91% specificity in detection of early HCC from controls at risk with AUC 0.87, independent of AFP (composite model including AFP increased AUC to 0.93). 63 Regarding the role of CTCs in early detection, a recent meta-analysis of 20 studies showed utility in CTC for diagnosis of HCC.…”
Section: Data On Clinical Applications Of Liquid Biopsy For Hcc Early...mentioning
confidence: 99%
See 1 more Smart Citation
“…Bojan Losic presented a method for the discovery of small RNA clusters (smRCs, pronounced smirks) expressed in circulating liver cancer EVs ( von Felden et al, 2021 ). The method is de novo , not relying on mapping reads to annotated RNAs.…”
Section: Exrna-seq Processingmentioning
confidence: 99%